The Being of the Master in Question: The alienation of pedagogical knowledge and teaching practices - Prieto Galindo, William Andrés; Loaiza Ortiz, Yessica Natalia; Ochoa Nuñez, María del Pilar; Pedreros Páez, Leidy Johanna (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
From the theoretical perspectives of Marx, Sartre and Foucault, this article reflects on the process by which the teacher is placed in a state of alienation regarding his pedagogical knowledge and his teaching practices. The contributions of the research group History of Pedagogical Practices are highlighted, formulating proposals to expand the field of discussion. Research by teachers is proposed as a valid, legitimate and pertinent strategy to promote an awareness of oneself and for oneself, based on non-alienated teaching practices, linked to a reflexively produced and created conceptual domain.